Colchicine use and the risk of CKD progression: a multicentre nested case-control study. (9th February 2022) - Kim, Hyung Woo; Joo, Young Su; Yun, Hae-Ryong; Kim, Jae Young; Jhee, Jong Hyun; Roh, Yun Ho; Park, Jung Tak; Chang, Tae Ik; Yoo, Tae-Hyun; Kang, Shin-Wook; Han, Seung Hyeok
Abstract: Objectives: Despite the preclinical evidence on protective effects of colchicine against kidney fibrosis, whether colchicine could delay the progression of chronic kidney disease (CKD) in humans remains unknown. This study examined the association between long-term colchicine use and risk of adverse kidney outcome in patients with CKD who were treated for hyperuricaemia or chronic gout. Methods: We conducted a multicentre, nested, case-control study in three Korean hospitals. Patients were aged ≥19 years; had CKD G3–G4; and used drugs including colchicine, allopurinol and febuxostat for hyperuricaemia or chronic gout during the period from April 2000 to October 2020. Patients with CKD progression, which was defined as ≥40% decrease from the baseline estimated glomerular filtration rate or the onset of kidney failure with replacement therapy, were matched to controls based on follow-up time, age and sex. Results: Overall, 3085 patients with CKD progression were matched to 11   715 control patients. Multivariate conditional logistic regression analysis showed that patients with ≥90 cumulative daily colchicine doses were associated with a lower risk of CKD progression [adjusted odds ratio (AOR), 0.77; 95% CI: 0.61, 0.96] than non-users. In the sensitivity analysis with matched CKD stages, the AOR was 0.77 (95% CI: 0.62, 0.97). This association was more pronounced in patients without diabetes or hypertension, and in patients with CKD G3. Conclusion: Colchicine use is associated with a lower risk of adverse kidney outcomes in CKD patients with hyperuricaemia, or chronic gout.